2022
DOI: 10.3389/fpubh.2021.755726
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Parental Social Integration on the Physical Examination Utilization for Young Migrant Children: A National Cross-Sectional Study in China

Abstract: Purpose: Physical examination is a key component of child health management. Migrant children are a vulnerable group with lower healthcare service utilization, and this study aims to explore the effect of parental social integration on the physical examination service utilization for young migrant children under 6 years old in China.Method: This study conducted a secondary data analysis of the 2014 National Internal Migrant Dynamic Monitoring Survey in China. A total of 2,620 participants were included in this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Two studies focused on identifying the social determinant of healthcare utilization using data from nationally representative health surveys in India and China ( 4 , 5 ). Specifically, using the fourth round of National Family Health Survey data, Madhumita and Soumitra ( 4 ) highlighted the disparities in maternal and child healthcare (MCH) among disadvantaged and advanced social groups in three states of India.…”
Section: Contribution To the Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies focused on identifying the social determinant of healthcare utilization using data from nationally representative health surveys in India and China ( 4 , 5 ). Specifically, using the fourth round of National Family Health Survey data, Madhumita and Soumitra ( 4 ) highlighted the disparities in maternal and child healthcare (MCH) among disadvantaged and advanced social groups in three states of India.…”
Section: Contribution To the Fieldmentioning
confidence: 99%
“…Limited accessibility and poor infrastructure came out as other barriers to the under-utilization of these healthcare services. However, Jing et al focused on assessing the effect of parental social integration on the physical examination service utilization for young migrant children in China using the 2014 National Internal Migrant Dynamic Monitoring Survey ( 5 ). Using four different dimensions of social integration, the authors found that parental social integration was associated with migrant children's physical examination utilization.…”
Section: Contribution To the Fieldmentioning
confidence: 99%
“…Both RUMC and UUMC are unable to enjoy social services in cities to the same extent as children with local urban Hukou [8]. This disadvantage manifests as limited access to public school education, medical insurance, and benefits typically available to children with local urban residency [7,9,10]. As an illustration, in 2021, only 43.7% of RUMC in China, who were within the nine-year compulsory education age group, were receiving education in public schools in their destination cities [11 && ].…”
Section: Introductionmentioning
confidence: 99%